Problem Gambling among Young People in Sub-Saharan Africa - Ssewanyana, Derrick; Bitanihirwe, Byron (Frontiers in Public Health, 2018)
Gambling is a cross-cultural and global activity which typically involves the wagering of money or an item of monetary value on an outcome that is governed by chance. Although gambling is positioned as a legitimate recreational and leisure activity within sub-Saharan Africa (SSA), there is widespread recognition among healthcare professionals and policy-makers that gambling has the capacity to become dysfunctional in a minority. Emerging knowledge suggests that problem gambling is rapidly evolving in to a public health concern in SSA, especially among youth. This article focuses on problem gambling among young people in SSA with an emphasis on three key themes: 1) gambling behaviour and patterns in SSA; 2) public health and socio-economic implications of gambling in SSA; and 3) public health policies and interventions for addressing this issue. We believe that collaborative efforts between government, prevention specialists, legislators, researchers, treatment providers, and other stake holders can influence the uptake of research findings necessary to implement social policies and design effective public health intervention options to combat problem gambling and its associated implications among young people in SSA.